A Pancreatic Fistula after the Laparoscopic Sleeve Gastrectomy - Gökhan Selçuk Özbalcı; Ayfer Kamalı Polat; İsmail Alper Tarım; Murat Derebey; Mehmet Selim Nural; Volkan Tümentemur; Ufuk Karabacak (Case Reports in Surgery)
Laparoscopic sleeve gastrectomy (LSG) is a popular surgical weight-loss procedure in the treatment of morbid obesity. There are some complications regarding this procedure in the literature. This report presents a pancreatic fistula (PF) case, which has not been previously seen.